Pelatihan Pemanfaatan Aplikasi Webalita sebagai Media Edukasi Tumbuh Kembang Balita Berbasis Website - Hervina Halimi; Sofiansyah Fadli; Ilham Kusuma Jaya; Muhamad Amiza Surya (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve the knowledge and skills of parents and posyandu cadres in utilizing the Webalita application as a web-based educational media for monitoring child growth and development. The main problem faced in the community is the limited access and understanding of digital educational tools that can practically and accurately support early childhood growth monitoring. The program was carried out through training and mentoring activities, which included: (1) socialization on the importance of monitoring child growth and development; (2) training on the use of the Webalita application; and (3) evaluation of participants’ understanding through questionnaires and hands-on practice. The results showed an increase in participants’ knowledge and skills in accessing, operating, and utilizing the Webalita application, with a score of 81.5%. Participants also responded positively to the application as it was considered helpful in providing educational information related to child growth and development. Therefore, this training can serve as a solution to support community health digital literacy through technology-based approaches.